2001
DOI: 10.1037/0033-3204.38.4.431
|View full text |Cite
|
Sign up to set email alerts
|

Resistance.

Abstract: This article reviews extant literature on how patient resistance has been defined and its effects on psychotherapy. Resistance has been considered as both a patient-in-treatment state and as an enduring trait. In either form, patient resistance seems to interfere with treatment outcome. Resistance also Junctions as a moderating variable in determining the effectiveness of different levels of therapist directiveness. The evidence that patients who enter treatment with high levels of traitlike resistance will be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
0
29
0
2
Order By: Relevance
“…Hill and Knox (2002) suggest that therapist self-disclosure should depend on client characteristics but there is no research that documents what these characteristics should be. Not surprisingly, when therapist behavior has not been responsive to pretreatment client characteristics (e.g., being directive with a resistant client), this has often resulted in poor treatment outcomes (Beutler, Rocco, Moleiro, & Talebi, 2001). However, as important as this probably is, a literature search revealed that very little work has examined the impact of client characteristics on therapist behavior in youth mental health treatment research.…”
Section: Client Pretreatment Characteristicsmentioning
confidence: 99%
“…Hill and Knox (2002) suggest that therapist self-disclosure should depend on client characteristics but there is no research that documents what these characteristics should be. Not surprisingly, when therapist behavior has not been responsive to pretreatment client characteristics (e.g., being directive with a resistant client), this has often resulted in poor treatment outcomes (Beutler, Rocco, Moleiro, & Talebi, 2001). However, as important as this probably is, a literature search revealed that very little work has examined the impact of client characteristics on therapist behavior in youth mental health treatment research.…”
Section: Client Pretreatment Characteristicsmentioning
confidence: 99%
“…Specifically, directiveness may occur when providers initially listen to consumers' goals, but ultimately make decisions and direct consumers in ways that are inconsistent with consumers' stated goals. Previous studies suggest that providers' directiveness can result in increased client resistance to treatment (Beutler et al 2001) and that less directiveness by therapists resulted in outcomes for reactant clients in treatment for alcoholism (Karno and Longabaugh 2005). For example, in a study of 51 consumers involved with mental health courts, Pratt et al (2013) found that consumers' perceptions of negative pressures (i.e., perceived injustices during court proceedings) from professionals statistically predicted their future involvement with the criminal justice system.…”
Section: Introductionmentioning
confidence: 96%
“…However, some patients may be reactant, where they feel as if a didactic approach can be an authoritative stance, which can lead to resistance (Brehm, 1976 ) , and some research has indicated that people with a propensity for such reactance do not fare as well with CBT (Beutler, Rocco, Moleiro, & Talebi, 2001 ) . Therapist behavior has been indicated to increase or decrease resistance (Patterson & Forgatch, 1985 ) , and a therapist's relational style can indeed impact patient motivation (Norcross, 2002 ) .…”
Section: Treatment Approaches To Address Issues With Motivation For Bmentioning
confidence: 98%